Cutaneous toxicities from targeted therapies used in oncology: Literature review of clinical presentation and management - Solène Huynh Dagher, MD; Astrid Blom, MD; Hedi Chabanol, MSC; Elisa Funck-Brentano, MD, PhD (Wolters Kluwer, 2021)
With the development of molecular targeted therapies, a wide array of dermatologic toxicities is appearing. Their prevention, recognition, and management by dermatologists is critical to ensure antineoplastic treatment continuation. The objective of this study was to provide a literature review of the most common dermatologic toxicities due to targeted therapies in oncologic patients, including their clinical presentation, prevention, and management.